PENGARUH KEJELASAN ANGGARAN, PENGENDALIAN AKUNTANSI DAN SISTEM PELAPORAN TERHADAP SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) KABUPATEN MUSI BANYUASIN (Studi Kasus Pada Sekretariat DPRD Kabupaten Musi Banyuasin). - Irfansyah, Ahmad; Septariani, Jumania (Institut Rahmaniyah Sekayu, 2024)
The research aims to see the influence of budget clarity, accounting control and reporting systems on the government agency performance accountability system (SAKIP) at the regional secretariat of Musi Banyuasin Regency. In this research, the author used a quantitative method, using a questionnaire by distributing 30 (thirty) questionnaires to respondents at the Musi Banyuasin Regency DPRD Secretariat. With the measurement technique using a Likert scale and statistics, the data processing uses SPSS For Windows Relase 15.0. The research results show that clarity of budget targets, accounting control and reporting systems influence the Government Agency Performance Accountability System (SAKIP). This can be seen from the regression results equation as follows: Y= 10,731 + 0.300 X1+ 0.208 X2 + 0.614 X3. This means that clarity of budget targets, accounting controls and a good reporting system will increase the value of SAKIP. It can be said that the higher the influence of the SAKIP value, the higher the clarity of budget targets, accounting controls and reporting systems. On the other hand, the lower the clarity of budget targets, accounting controls and reporting systems, the lower the value of SAKIP. Based on the calculation results, the fcount value is 15.502 with a significance level of 0.000 (below 0.05) or fcount is greater than ftable = 2.975154. Paying attention to the results of this test, the hypothesis states that clarity of budget targets, accounting control and reporting systems simultaneously make a significant contribution to SAKIP.